Highly flexible and stretchable thermally conductive composite film by polyurethane supported 3D networks of boron nitride. (10th November 2017) - Hong, Hye-Jin; Kwan, So Mang; Lee, Dong Su; Kim, Seung Min; Kim, Yun Ho; Lim, Jin Seong; Hwang, Jun Yeon; Jeong, Hyeon Su
Abstract: Current interest in flexible and stretchable electronics has been amplified because of their remarkable features for numerous applications. Accordingly, compliant efficient thermal management for such electronics is in great demand. However, new materials simultaneously coping with high thermal conductivity and mechanical flexibility have not been sufficiently studied. Here, we report a simple yet highly efficient method to construct three-dimensional (3D) hexagonal boron nitride (h-BN) network in a polymer composite, which is both thermally conductive and mechanically stretchable. 3D h-BN network is easily fabricated by in-situ incorporation of h-BN onto the surface of a water-borne polyurethane (PU) scaffold during polymerization. The 3D h-BN network in the composite film offers high thermal conductivity up to 10 W/m·K while the PU contributes excellent mechanical flexibility such as folding, twisting and stretching. Moreover, the process developed in this study is highly economical and processable to be scaled up without the need of complex equipment or procedure, which will be of great interest to current manufacturing as well as soft and stretchable electronic devices. Graphical abstract: